The Effect of Conventional and Nanoformulation Herbicide on Sphagneticola Trilobata - Hasrin, Nur Syahiidah Aqilah; Shah, Nor’aishah Abu; Dzulkifli, Nur Nadia; Fatimah, Is; Sheikh Mohd Ghazali, Sheikh Ahmad Izaddin (Trends in Sciences, 2023)
The conventional herbicide 2-methyl-4-chlorophenoxyacetic acid (MCPA) provide substantial risk to the environment such as contamination of soil and groundwater. The overuse application of conventional herbicide can leave harmful residues in soil and be washed off as runoff, thus causes toxic effect to nontarget organism. For instance, MCPA can cause toxicity to the freshwater organisms such as Daphnia magna and alga Selenastrum capricornutum. Zinc oxide as nanomaterials that are intercalated with 2-methyl-4-chlorophenoxyacetic acid (ZMCPA) herbicide may be useful to resolve the problems associated with MCPA. Nanoherbicide are known to provide a better penetration of active substances hence reduces the amount of herbicide to be applied. The nanostructured herbicide such as ZMCPA could substantially replace the conventional herbicide MCPA if it able to kill the targeted weeds efficiently and have a low risk to the environment. Therefore, it is important to compare the differences of herbicidal activity of MCPA and ZMCPA. The objective of this research is to determine the effects of MCPA and ZMCPA on growth and pigment content of Sphagneticola trilobata. The 2nd objective of this research is to measure the physiological effect and effectiveness of herbicidal activity between the conventional and nanoformulation against Sphagneticola trilobata. The preliminary study was conducted to determine a minimal concentration for MCPA to exert its effect on Sphagneticola trilobata. Then, in the main research, Sphagneticola trilobata was exposed to different concentrations of MCPA and ZMCPA in low, medium and high concentrations. The effect of MCPA and ZMCPA on growth and pigment content of Sphagneticola trilobata was observed at 7, 14 and 21 days, respectively. The results indicated there were no obvious differences in plant growth and pigment content observed between treatment of MCPA and ZMCPA at the same exposure concentration at 7, 14 and 21 days, respectively. MCPA showed higher herbicide efficacy than ZMCPA. HIGHLIGHTS Nanoherbicide Development: The intercalation of zinc layered hydroxide (ZLH) with MCPA resulted in ZMCPA, a nanoherbicide with improved delivery and penetration capabilities compared to conventional herbicides. Potential Replacement for Conventional Herbicides: Nanostructured herbicides like ZMCPA have the potential to replace conventional herbicides like MCPA due to their numerous benefits in addressing issues associated with traditional herbicides. Comparable Herbicidal Effectiveness: The study evaluated the herbicidal activity of MCPA and ZMCPA on Sphagneticola trilobata and found that both formulations inhibited the growth of the weed to a similar extent after 7, 14, and 21 days, indicating comparable efficacy between the conventional and nanoformulation herbicides. GRAPHICAL ABSTRACT